Destabilization of interaction between cytokinin signaling intermediates AHP1 and ARR4 modulates Arabidopsis development. Issue 2 (30th January 2015) - Verma, Vivek; Sivaraman, Jayaraman; Srivastava, Anjil Kumar; Sadanandom, Ari; Kumar, Prakash P.
Summary: Eukaryotic two‐component signaling involves the His–Asp–His–Asp multistep phosphorelay (MSP). In Arabidopsis thaliana, cytokinin‐mediated MSP signaling intermediates include histidine kinases (HKs), histidine phosphotransfer proteins (Hpts) and response regulators (RRs). The structure–function relationship of interaction between Hpt (e.g. AHP1) and RR (e.g. ARR4) is poorly understood. Using a homology model and yeast two‐hybrid analysis, we identified key amino acids of ARR4 at the AHP1–ΔARR4 (16–175) interaction interface. Mutating them in Arabidopsis ( arr3, 4, 5, 6, 8, 9 hextuple mutant background) and performing root length assays provided functional relevance, and coimmunoprecipitation (coIP) assay provided biochemical evidence for the interaction. The homology model mimics crystal structures of Hpt–RR complexes. Mutating selected interface residues of ARR4 either abolished or destabilized the interaction. D45A and Y96A mutations weakened interaction with AHP1, and exhibited weaker rescue of root elongation in the hextuple mutants. CoIP analysis using cytokinin‐treated transgenic Arabidopsis seedlings provided biochemical evidence for weakened AHP1–ARR4 interaction. The relevance of the selected residues for the interaction was further validated in two independent pairs of Hpt–RR proteins from Arabidopsis and rice ( Oryza sativa ). Our data provide evidence of a link between Hpt–RR interaction affinity and regulation of downstream functions of RRs. This establishes a structure–function relationship for the final step of a eukaryotic MSP signal cascade.